Spectral analysis of some classes of multivariate random fields with isotropic property - Ponomarenko, O.; Perunk, Y. (Інститут математики НАН України, 2006)
In this paper we consider two classes of generalized random ﬁelds of second order on R^n with values in Hilbert space H with isotropic property: ﬁrst - exponentially convex and isotropic random ﬁelds and second - homogeneous and isotropic random ﬁelds. The spectral representations for such ﬁelds and their covariance are obtained.